Cotton and honey bees in a single mutually beneficial biocenosis (Eurasian Research Bulletin, 2022)
The article presents the results of the author's theoretical and field research and the experience of foreign countries in studying the pollination of cotton varieties by bees and their nectar productivity. Field studies on the study of the nectar productivity of cotton varieties and their cross-pollination by bees were carried out in two farms in the Alat district of the Bukhara region. The results of the research established the relationship between the ten-day pollinating activity of bees with the seasonal nature of nectar secretion and varietal differences in nectar content. A technique has been developed for placing crossed cotton varieties in the cross-pollination area.